Implementation of Interpretation of Financial Accounting Standards (ISAK) 35 on The Financial Statements of Non-Profit Entities - Chivalrind Ghanevi Ayuntari; Anis Fitri Amin; Rizky Maulana (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the implementation of the Financial Accounting Standard Interpretation (ISAK) 35 in the financial statements of a non-profit entity, namely Foundation XX. This research is quantitative in nature. The data source consists of secondary data in the form of financial statements. The analysis was conducted by comparing the implementation of ISAK 35 in the financial statements of Foundation XX for the years 2021 and 2022 with ISAK 35. The results indicate that the preparation of financial statements for the years 2021 and 2022 at Foundation XX has adhered to ISAK 35, particularly in the cash flow statements and notes to the financial statements. However, in the statement of financial position, statement of comprehensive income, and statement of changes in net assets, there are some aspects that do not comply with ISAK 35. These discrepancies are due to the absence of certain accounts in the financial statements, which is a result of the lack of transactions related to those accounts.